Technology Acceptance Model to Measure Perception Use of Electronic Nursing Documentation - Zakiyah, Ana (STIKES Adi Husada, 2024)
Electronic Nursing Documentation (END) use in hospitals has increased along with the development of technology. Hence, nursing education needs to synergize to adopt the use of END. However, preceptors have varying perceptions regarding their application in nursing clinical practice. The study aims to determine the preceptor's perception of using END based on the Acceptance Model (TAM) Technology. In the descriptive research design, the population is clinical preceptors in hospitals, and purposive sampling was used to obtain a total of 90 samples. The research instruments used Perceived Usefulness (PU) and Perceived Ease of Use (PEOU). The analysis uses frequency distribution. The study's results on the PU variable obtained the perception of the preceptor about the use of END in all indicators, generally in the high category of more than 90%. In the PEOU variable, most clinical preceptors had a moderate perception of the clarity indicator 71 (78.9%), and a high perception of the flexibility of use indicator as much as 69 (76.7%). A positive perception of technology can be formed if users find the technology practical and easy to use.